The Effect of Employee Satisfaction and Performance on Green Work Behaviour: A Literature Review - Laksana, Michael Ardian; Kurniawan, Herdi; Mas’ud, Fuad (LifeSciFi, 2024)
With the growing emphasis on environmental sustainability, organizations are increasingly adopting Green Human Resource Management (GHRM) practices. GHRM integrates environmental management with HR functions, embedding sustainable policies that promote ecological responsibility among employees. This literature investigates the links between employee satisfaction, job performance, and eco-friendly work behaviours in the GHRM framework, employing quantitative research methods. Through sustainable HR practices, GHRM cultivates environmental awareness within workplaces. By analysing survey data and performance metrics, the review examines how employee satisfaction impacts performance and, subsequently, supports green work behaviours. The findings reveal a positive correlation amongst employee satisfaction and job performance, with significant influence on environmentally responsible behaviours. Future studies should focus on developing targeted strategies to enhance these outcomes, strengthening GHRM’s role in promoting sustainability and driving improved organizational performance.